Szintigraphie mit111 ln-markiertem Antimyosin bei Churg-Strauss-Vaskulitis mit myokardialer Beteiligung - Krause, Th.; Schümichen, C.; Beck, A.; Lang, B.; Hohnloser, S.; Moser, E. (Nuklearmedizin - NuclearMedicine, 1990)
A case of Churg-Strauss vasculitis in a young woman is reported. Diagnosis was confirmed by muscle biopsy. Affection of lungs, kidneys and skin was evident. In addition, myocarditis was suspected on clinical evidence. A highly positive scintigraphy with 111 In-anti myosin enabled diagnosis and assessment of damage to the myocytes. With a heart-to-lung ratio of 3.0 the accumulated activity in the myocardium was higher than usually found in myocarditis. This finding supports the hypothesis of an additional ischemic necrosis.